Transcatheter aortic valve implantation complexity score - Christopher Malkin; Daniel J Blackman; Noman Ali; Amr Abdelrahman; Michael Cunnington; Paul Bamford; Sacchin Arockiam; Suleman Aktaa; Rowan Hall (Open Heart)
Background Increasing demand for transcatheter aortic valve implantation (TAVI) places greater emphasis on the efficiency of pathways and services. A significant limitation to increasing TAVI capacity is the availability of cardiac catheterisation laboratory time. We have developed a novel complexity scoring system (TAVI ComplEXity; TEX score) which can aid in planning lists with appropriate case selection. To validate the TEX score, we have undertaken a retrospective analysis of TAVI cases. The hypothesis is that increasing TEX score correlates with increased procedural duration and reduced valve academic research consortium (VARC) 3 technical and device success.Methods The TEX score assigns patients to a complexity level of 1 (low), 2 (intermediate) or 3 (high) based on the presence of specific clinical and anatomical variables. For validation purposes, comparisons were made between patients in the three complexity levels with respect to procedural duration as well as VARC-3 technical success, device success and early safety.Results The validation study included 1034 consecutive patients who underwent TAVI between June 2021 and October 2023. Of these, 582 (56.3%) were classified as level 1 complexity, 377 (36.5%) level 2 and 75 (7.3%) level 3. Significant differences were observed between the three groups with respect to procedural duration (73.7 min vs 85.6 min vs 136 min; p<0.001), VARC-3 technical success (97.9% vs 96.6% vs 92%; p<0.05) and VARC-3 device success (96.2% vs 92.3% vs 86.6%; p<0.001).Conclusion The TEX score is a simple tool which allows stratification of patients into three levels of complexity. Increasing complexity levels correlate with increasing procedural duration and reduced VARC-3 technical and device success. This is potentially useful for scheduling patients onto appropriate lists.